Extraintestinal lymphoma in association with Whipple's disease. Issue 11 (November 1993) - Gillen, C D; Coddington, R; Monteith, P G; Taylor, R H
Abstract : A 45 year old man is described with Whipple's disease who presented with weight loss, lethargy, and ascites. He subsequently developed fever and a mass in the neck, but died despite antibiotic treatment and nutritional support. Necropsy showed extraintestinal lymphoma.